Mesenchymal Stromal Cell Secretome for Post-COVID-19 Pulmonary Fibrosis: A New Therapy to Treat the Long-Term Lung Sequelae? - Bari, Elia (Cells, 2021)
To date, more than 100 million people worldwide have recovered from COVID-19. Unfortunately, although the virus is eradicated in such patients, fibrotic irreversible interstitial lung disease (pulmonary fibrosis, PF) is clinically evident. Given the vast numbers of individuals affected, it is urgent to design a strategy to prevent a second wave of late mortality associated with COVID-19 PF as a long-term consequence of such a devastating pandemic. Available antifibrotic therapies, namely nintedanib and pirfenidone, might have a role in attenuating profibrotic pathways in SARS-CoV-2 infection but are not economically sustainable by national health systems and have critical adverse effects. It is our opinion that the mesenchymal stem cell secretome could offer a new therapeutic approach in treating COVID-19 fibrotic lungs through its anti-inflammatory and antifibrotic factors.